Rancang Bangun Sistem Steganografi Multi-format LSB dan Enkripsi Fernet Berbasis Python - Divaul Khairah; Melinda Melinda; Isyatul Muna; Kharina Kharina (JIKUM: Jurnal Ilmu Komputer, 2026)
This research designs a data security system using Python by integrating Fernet Encryption and LSB Steganograph. The system features multi-format capabilities, allowing users to embed text or files into image and audio media. The process begins by encrypting data using a password-based key, which is then embedded into the least significant bits of the carrier media. Experimental results demonstrate that the system effectively maintains data confidentiality with high visual quality. However, the embedding capacity is strictly limited by the size of the carrier media; oversized files cannot be processed if they exceed the available LSB bit space. This system provides an effective solution for small to medium- scale data protection through double-layer security.